2017
DOI: 10.1007/s00240-017-0966-1
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive percutaneous nephrolithotomy vs standard PCNL for management of renal stones in the flank-free modified supine position: single-center experience

Abstract: To assess the safety and efficacy of minimally invasive percutaneous nephrolithotomy (mPCNL) as compared to standard PCNL (sPCNL) for management of 2-3-cm renal stones in the flank-free modified supine position. Between September 2010 and December 2013, 150 patients (168 renal units) with 2-3-cm renal stones were prospectively randomized into two treatment groups; Group A (75 patients/87 renal units) treated by mPCNL and Group B (75 patients/81 renal units) treated by sPCNL. In both groups, the patients were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 13 publications
2
34
0
1
Order By: Relevance
“…Minimally invasive PCNL, which requires dilation to within 20‐Fr, provides greater safety because of the lower incidence of bleeding that necessitates blood transfusion than standard PCNL. It also has an operative time and SFR that are comparable with those for standard PCNL Yamaguchi et al . reported that the incidences of blood transfusion associated with the use of <18, 24–26, 27–30 and 32–34‐Fr tract sheaths were 1.1%, 4.8%, 5.9% and 12.1%, respectively ( P < 0.0001).…”
Section: Percutaneous Nephrolithotomy: Pcnl and Ecirsmentioning
confidence: 73%
See 1 more Smart Citation
“…Minimally invasive PCNL, which requires dilation to within 20‐Fr, provides greater safety because of the lower incidence of bleeding that necessitates blood transfusion than standard PCNL. It also has an operative time and SFR that are comparable with those for standard PCNL Yamaguchi et al . reported that the incidences of blood transfusion associated with the use of <18, 24–26, 27–30 and 32–34‐Fr tract sheaths were 1.1%, 4.8%, 5.9% and 12.1%, respectively ( P < 0.0001).…”
Section: Percutaneous Nephrolithotomy: Pcnl and Ecirsmentioning
confidence: 73%
“…It also has an operative time and SFR that are comparable with those for standard PCNL. 83 Yamaguchi et al reported that the incidences of blood transfusion associated with the use of <18, 24-26, 27-30 and 32-34-Fr tract sheaths were 1.1%, 4.8%, 5.9% and 12.1%, respectively (P < 0.0001). Therefore, the mini-PCNL, which uses a smaller tract sheath, was introduced to decrease the bleeding risk.…”
Section: Complications and Preventive Measures For Pcnlmentioning
confidence: 99%
“…[ 10 , 11 , 16 , 18 ] To determine whether the vacuum effect affected the results, 10 RCTs were divided into 2 sub-groups (vacuum suction group [VSG] [ 12 , 17 , 18 ] and non-vacuum suction group [NVSG]). [ 10 , 11 , 13 , 14 , 15 , 16 , 19 ] To determine whether type and quantity of stones affected the results, we extracted SFR and operative time in 4 studies to conduct our meta-analysis. [ 10 , 11 , 16 , 18 ] Relevant characteristics and baseline of articles are listed in Table 1 , and the process of identifying RCTs is displayed in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…mPCNL is de ned as PCNL performed using Amplantz sheaths with a diameter of 14-20 Fr [3,51]. mPCNL has the advantage of reducing complications that may arise from larger instruments and sheaths [4].…”
Section: Discussionmentioning
confidence: 99%